TRANSFORMASI RITUAL MOSEHE WONUA DI KABUPATEN KOLAKA - Arifin, Munaser; Dirman, La Ode; Aso, La (Universitas Halu Oleo, 2021)
Abstract: Cultural transformation becomes wide open in the midst of society to be investigated. The people of Kolaka Ethnic Mekongga District have a mosehe wonua ritual as a space of cultural expression that grows over a long period of time and then undergoes transformation. The formulation of the problem in this study are: 1) how are the forms of transformation of the Wonua Mosehe ritual in Kolaka Regency, and 2) What are the factors that cause the transformation of the Mosehe Wonua ritual in the Kolaka Regency. This study aims to describe and analyze the forms of transformation of the Wonua mosehe ritual in Kolaka District, and describe and analyze the factors that cause the transformation of the Wonua Mosehe ritual in Kolaka District. As a basis for analysis, this study uses the theory of cultural transformation. This study uses a qualitative approach with data collection methods using observation techniques, in-depth interviews, and documentation. The results of this analysis show that the forms of mosehe wonua ritual transformation include three things, namely: 1) transformation in aspects of knowledge, 2) transformation in technological aspects, and 3) transformation in aspects of ritual presentation. While the factors causing the transformation are caused by three things, namely: 1) educational factors, 2) ideological factors of community religiosity, and 3) cultural innovation factors.Keywords: Transformation, Ritual, Mosehe Wonua